2021
DOI: 10.1093/nar/gkab638
|View full text |Cite
|
Sign up to set email alerts
|

CellCall: integrating paired ligand–receptor and transcription factor activities for cell–cell communication

Abstract: With the dramatic development of single-cell RNA sequencing (scRNA-seq) technologies, the systematic decoding of cell-cell communication has received great research interest. To date, several in-silico methods have been developed, but most of them lack the ability to predict the communication pathways connecting the insides and outsides of cells. Here, we developed CellCall, a toolkit to infer inter- and intracellular communication pathways by integrating paired ligand-receptor and transcription factor (TF) ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(104 citation statements)
references
References 80 publications
2
102
0
Order By: Relevance
“…Intercellular signaling among different immune cell types of sepsis and sepsis-induced ARDS was calculated by CellCall [ 20 ], which is a toolkit for recognition of intercellular communication networks and internal regulatory signals by combining the expression of ligands/receptors with downstream transcription factor (TF) activities for certain ligand–receptor (LR) pairs. Genes that were expressed in less than 10% of the cells of a certain cell type were excluded in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Intercellular signaling among different immune cell types of sepsis and sepsis-induced ARDS was calculated by CellCall [ 20 ], which is a toolkit for recognition of intercellular communication networks and internal regulatory signals by combining the expression of ligands/receptors with downstream transcription factor (TF) activities for certain ligand–receptor (LR) pairs. Genes that were expressed in less than 10% of the cells of a certain cell type were excluded in this study.…”
Section: Methodsmentioning
confidence: 99%
“…For a given signaling pathway, a receiver cell responds to signals from a sender cell by triggering downstream gene responses, including altered transcription factor activity and target gene expression. While most of the existing methods infer intercellular communication based only on expression of ligand-receptor pairs, several methods have recently taken into account the intracellular downstream response in receiver cells [27,[32][33][34][35][36][37] (Figure 1). These methods could reduce false-positive communications by considering the expression of genes for each receptor, transcription factor (TF) and target genes involved in a particular pathway.…”
Section: Computational Approaches For Cell-cell Communication Inferen...mentioning
confidence: 99%
“…However, it has been now shown that immune cells can display pro-or anti-tumour effector functions, with the final outcome being tumour suppression or progression and metastasis, depending on the number, spatiotemporal distribution of relevant immune cells, and the type and/or stage of cancer. Intercellular communication between tumour and immune cells, either through direct cell-cell interactions or the release of soluble cytokines and growth factors, is the basis of mechanisms that tumour cells use to induce tolerance and suppression of anti-tumour responses [117,118]. Adding to this complex scenario, recent studies have highlighted the important role of the metabolic state within the TME [119].…”
Section: The Role Of Citrate On Tumour-infiltrating Immune Cellsmentioning
confidence: 99%